Jorge de Sena and the Spanish literary exile - Vieira, Inês Espada (2019)
Starting from the concept of exile, in this essay we explore Jorge de Sena as an hispanist. Critic and translator, he had a deep knowledge of Spanish authors and Spanish culture, maintaining regular contact with members of the Spanish intelligentsia in particular in the USA, both at personal level and via letter exchanges.